Cybersecurity of Sensors on Smart Vehicles: Review of Threats and Solutions - Putro, Prasetyo Adi Wibowo; Amelia, Fetty; Pidanič, Jan; Suhartanto, Heru; Rahardjo, Imam Arif; Imandeka, Ejo (IEEE (Institute of Electrical and Electronics Engineers), 2023)
The use of sensors in smart vehicles brings benefits and vulnerabilities. Different kinds of sensors in smart vehicles are vulnerable to cyber-attack. Until now, the investigation of challenges and solutions for in-vehicle cybersecurity hasn’t discussed various sensor objects and their correlation. In this study, we studied the cyber security problems of sensors in smart vehicles and how to overcome them. The research was designed as Systematic Literature Review (SLR) using the Kitchenham methodology with modification in the filtering phase using the artificial intelligence application, Elicit, to identify the problems, conclusions, and methodology description. Seventeen publications from 2016 until 2023 were gained from five databases. As a result, we find that the most discussed object related to cybersecurity sensors on smart vehicles are Electronic Control Units. Spoofing and jamming is still the most addressed threat, and machine learning is the most utilized solution to be implemented in detection systems. Advanced detection systems are incorporating updated attack models. We also suggest using updated attack models and machine learning algorithms to ensure the safety and security of smart vehicle technology. All identified sensor technology correlated using mind maps under the Intelligent Transport System theory.
Kybernetická bezpečnost senzorů v inteligentních vozidlech: Přehled hrozeb a řešení
Keywords: sensor, smart vehicles, threat, solution, cybersecurity, SLR, Kitchenham; senzor, chytrá vozidla, hrozba, řešení, kybernetická bezpečnost, SLR, Kitchenham